Small sided games in soccer - a systematic review - Sarmento, H.; Clemente, F. M.; Harper, L. D.; da Costa, I. T.; Owen, A.; Figueiredo, A. J. (International Journal of Performance Analysis in Sport, 2018)
The purpose of this paper was to systematically review and organise the literature on soccer SSGs, in order to ascertain the most frequently researched topics, characterise the methodologies employed, and systematise the evolution of the related research areas.